Dampak Polusi Udara terhadap Kesehatan Manusia - Farhatun Haya; Khaira Nisa; Rio Febrian Ladipasa; Ari Suriani; Afriza Media (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Air pollution is one of the most pressing environmental issues with significant impacts on human health. This study aims to examine the relationship between air pollution levels and human health disorders, as well as to identify effective mitigation solutions. Using a descriptive qualitative approach, data were collected through literature reviews from various journals, WHO reports, and other official sources. The analysis shows that exposure to air pollutants, particularly fine particulate matter (PM2.5), carbon monoxide, nitrogen dioxide, and ozone, can trigger respiratory, cardiovascular, and mental health disorders, and adversely affect children and pregnancies. These impacts are both short-term and long-term, including increased premature mortality and reduced quality of life. To minimize these effects, strategic solutions are needed, such as strengthening emission regulations, promoting eco-friendly transportation, using air purifiers, developing green open spaces, and providing public education. This study emphasizes the importance of collaboration between the government, society, and the private sector in creating clean air and a sustainably healthy environment.